دور التسويق الداخلي في تحقيق رضا العملاء - - غميض نوال (جامعة محمد بوضياف المسيلة, 2015)
Internal marketing includes a variety of methods and procedures uses so as to attract better qualified enterprise. In addition, the institution cares about the needs and the desires of the enterprise in order to satisfy them and hence to satisfy clients. This letter is addressed in three problematic chapters the role of the internalmarketingin gaining (receiving)the satisfaction of the client. We have chosen the banking agencie (BEA) in M’sila to try to know the level of implementation of the internal marketing methods, and its effects on consumers’ satisfaction. In order to address various aspects of the topic, several tools have been carried out: office surveys in the theatrical side views of a sample of staff and consumers in the practical side. This research has allowed us to draw important results which give the studied banking agencies some recommendation and proposals so as to improve the quality of their services and to gain (receive) consumers satisfaction and thereby achieve their objectives.
دراسة ميدانية في بنك الجزائر الخارجي وكالة المسيلة-
Keywords: internal marketing,customer satisfaction, employee satisfaction.